2012
DOI: 10.1103/physrevlett.108.246403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Hybridization Gap and Fano Resonance in the Kondo LatticeURu2Si2

Abstract: The nature of the second order phase transition that occurs in URu 2 Si 2 at 17.5 K remains puzzling despite intensive research over the past two and half decades. A key question emerging in the field is whether a hybridization gap between the renormalized bands can be identified as the long-sought 'hidden' order parameter. We report on the measurement of a hybridization gap in URu 2 Si 2 employing a spectroscopic technique based on quasiparticle scattering across a ballistic metallic junction. The differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
90
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 57 publications
24
90
1
Order By: Relevance
“…Schmidt et al (12) find a light band crossing the Fermi surface above 17.5 K turning into a hybridized heavy band only below the hidden-order transition. This finding contradicts the conventional view that mass builds up gradually below T K , although there have been recent reports of some hybridization occurring in the 25-30 K region by Park et al (14) and Levallois et al (15), but the reported effects are weak and perhaps not resolved by all spectroscopies. We can test the development of mass by carefully tracking the Drude weight as a function of temperature with optical spectroscopy.…”
contrasting
confidence: 55%
“…Schmidt et al (12) find a light band crossing the Fermi surface above 17.5 K turning into a hybridized heavy band only below the hidden-order transition. This finding contradicts the conventional view that mass builds up gradually below T K , although there have been recent reports of some hybridization occurring in the 25-30 K region by Park et al (14) and Levallois et al (15), but the reported effects are weak and perhaps not resolved by all spectroscopies. We can test the development of mass by carefully tracking the Drude weight as a function of temperature with optical spectroscopy.…”
contrasting
confidence: 55%
“…(1)] reveals the existence of an almost temperature-independent hybridization gap shifted from the Fermi-energy [19] and a pseudo-gap at the Fermi-energy which rapidly appears below the transition temperature [20]. …”
Section: An Approximate Ground Statementioning
confidence: 99%
“…Their enhanced effective masses (m * = 8 − 25m 0 ) 7,8 cannot adequately be described by band structure calculations (m b ≤ 8m 0 ) 7 although the latter give a Fermi surface sheet topology in agreement with dHvA and SdH experiments 1,6 . Conceptually mass enhancement can be obtained within the Anderson lattice model in constrained mean field approximation 38 which also leads to a narrow indirect hybridization gap close to the Fermi level, equivalent to the Kondo temperature (T K 11.1 meV or 129 K) that can be seen in STM experiments 20,39 . Here we are primarily interested in the very low energy magnetic response of the heavy quasiparticle ω ∆ HO = 4.1 meV which is considerably smaller than the Kondo temperature T K = 2.7∆ HO .…”
Section: Two Orbital Model For Hidden Order and Heavy Quasiparticmentioning
confidence: 99%